Analisis Kaidah Pembelajaran Dalam Al-Qur’an Sebagai Acuan Bagi Guru Dalam Membentuk Karakter Peserta Didik - Alexa Ayu Dewanda; Chadiza Azzahra Lubis; Hanestesia Zahara; Resya Eka Putri; Wismanto Wismanto (Jurnal Budi Pekerti Agama Islam, 2024)
A method is a set of methods or methods that teachers use in learning so that students can achieve certain learning goals and skills. Many verses in the Koran explain the use of methods in teaching. Some of them we find in Surah Ali Imran verse 159 and Al-Maidah verse 67. The aim of this research is to find out the method of learning or teaching the Al-Qur'an. This research method uses descriptive qualitative methods with a literature review. The main data sources come from books, magazines and the latest articles related to this research theme. The results of this research indicate that the methods of teaching the Al-Quran are (1) Hiwar, namely alternating conversations between two or more parties through questions and answers regarding a topic leading to a goal, and (2) Tabligh, namely a systematic, orderly and measurable method used by preachers in presenting tabligh material to their audiences.